Memory and attention during an alcohol hangover - Devenney, Lydia E.; Coyle, Kieran B.; Verster, Joris C. (Human psychopharmacology, 2019)
Objective This study aims to investigate attention, memory functioning, and mood in a natural setting with real‐life alcohol consumption levels. Methods Seventy‐four participants with a mean (SD) age of 24.5 (7.0) years old participated in a naturalistic study. A between subjects design was applied comparing a hangover group with an (alcohol‐free) control group. Participants in the hangover group consumed a mean (SD) of 13.8 (10.2) alcoholic drinks the night before testing. Cognitive tests included the Stroop test, Eriksen's flanker test, a divided attention test, intradimensional–extradimensional set shifting test, spatial working memory test, and free word recall test. Results The hangover group had increased reaction times compared with the control group. Selective attention (Stroop and Eriksen's Flanker test performance) was significantly impaired during alcohol hangover. However, the number of errors did not differ significantly between the groups in any task. Mood assessments revealed that the hangover group reported significantly higher levels of drowsiness and clumsiness compared with the control group. Conclusion Selective attention was significantly impaired during alcohol hangover. The differences between the hangover and control group did not reach significance for other forms of attention or memory.